Exercise-Induced Cardioprotection via eNOS: A Putative Role of Red Blood Cell Signaling - Suvorava, Tatsiana; Cortese-Krott, Miriam M. (Current Medicinal Chemistry, 2018)
Moderate exercise training is a key aspect of primary and secondary prevention strategies. Shear-induced upregulation of eNOS activity and function in the vascular endothelium is considered as one of the main molecular mechanisms of exercise-induced protection against myocardial ischemia/ reperfusion (I/R) injury. It has been reported that levels of plasma nitrite, which are largely dependent on eNOS activity, were increased in healthy subjects after acute exercise, while this increase was abolished in coronary artery disease (CAD) patients. Our group and others demonstrated that RBCs contain a functional eNOS, which contributes to systemic nitrite homeostasis and to cardioprotection; moreover, expression and activity of red cell eNOS are decreased in CAD patients and significantly correlated with flow-mediated dilation, a diagnostic marker of endothelial function. Therefore, in addition to vascular eNOS, also red cell eNOS (or in more general terms NO metabolic activity of RBCs) may play a role in exercise-dependent changes of NO-bioavailability. In this review, we will focus on what is known and what is unknown about the role of RBCs in exercise-dependent cardioprotection with emphasis on RBC signaling and red cell eNOS. In detail, we will discuss the effects and molecular mechanisms of shear stress and exercise training on RBC signaling and function, review how these changes may influence blood rheology and systemic hemodynamics and highlight the potential role of red cell eNOS-mediated cardiovascular protection induced by physical activity against myocardial injury in animal and human studies and in clinical settings.
Keywords: ischemia/reperfusion